ANALYSIS OF THE INFLUENCE OF ENVIRONMENTAL EXPENDITURE AND ENERGY CONSERVATION THROUGH GRDP ON ENVIRONMENTAL QUALITY INDEX ON JAVA AND BALI ISLAND - Estining Sholeha, Atika; Aji Suseno, Deky (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The objective of this paper is as follows: analyse the effect of government spending on environmental protection and energy conservation through Gross Regional Domestic Product (GRDP) on the Environmental Quality Index (EQI). This paper includes panel data on government spending on environmental protection and energy conservation as independent variables, GRDP as an intervening variable, and EQI as a dependent variable in Java and Bali Island in 2015-2023 using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study found a significant positive effect between government spending on environmental protection on GRDP and energy conservation on EQI. When the government spends the budget on environmental programmes, the currency circulating in the community can create jobs, thereby increasing local revenue. In addition, increasing the use of energy, especially renewable energy, also supports the creation of a healthier and more sustainable environment. The results find no evidence for a positive effect of energy conservation on GRDP, government spending on environmental protection on EQI, and GRDP on EQI. We conjecture that weak institutional quality can explain these results.